Amplificadores Raman em fibras microestruturadas - Castellani, Carlos Eduardo Schmidt (2009)
The development of microstructured fibers, also known as photonic crystal fibers (PCF), which has happened principally during the last decade, has raised new possibilities on the field of optics and telecommunications due to its capability of presenting some constructive parameters with non conventional values. In the context of optical communications, more precisely on the construction of optical amplifiers, these photonic crystal fibers also have brought some new interesting possibilities. Due to its capability of at the same time presents very high negative dispersion and high non linearity, it allows for example, the construction of Raman amplifiers with high gains that also compensate dispersion with reduced fiber lengths. The conventional silica-based fibers need tens of kilometers of fiber length to accomplish the same task. Taking advantage of that situation, the main purpose of this dissertation is exactly the project and the study of multi-pump Raman amplifiers operating as discrete devices providing gain and compensating dispersion over the entire C band, using a PCF. In order to project such amplifiers, an optimization technique made through an exhaustive search based on an analytical solution method for the signal propagation is proposed. The analysis of these amplifiers is made via computational simulations that are done with numerical and also analytical models, by means of the verification of the gain, ripple, optical signal to noise ratio (OSNR), and eye penalty parameters. Their performance is also evaluated by comparing the performance of a Raman amplifier operating with a conventional dispersion compensating fiber (DCF).